The morphology, behaviour and molecular phylogeny of Phytophthora taxon Salixsoil and its redesignation as Phytophthora lacustris sp. nov. (31st May 2012) - Nechwatal, J.; Bakonyi, J.; Cacciola, S. O.; Cooke, D. E. L.; Jung, T.; Nagy, Z. Á.; Vannini, A.; Vettraino, A. M.; Brasier, C. M.
<x xml:space="preserve">Abstract</x> Since its first isolation from Salix roots in 1972, isolates of a sexually sterile Phytophthora species have been obtained frequently from wet or riparian habitats worldwide and have also been isolated from roots of Alnus and Prunus spp. Although originally assigned to Phytophthora gonapodyides on morphological grounds, it was recognized that these isolates, informally named P. taxon Salixsoil, might represent a separate lineage within ITS Clade 6. Based on phylogenetic analyses and comparisons of morphology, growth‐temperature relationships and pathogenicity, this taxon is formally described here as Phytophthora lacustris sp. nov. Isolates of P. lacustris form a clearly resolved cluster in both ITS and mitochondrial cox1 phylogenies, basal to most other Clade 6 taxa. Phytophthora lacustris shares several unusual behavioural properties with other aquatic Clade 6 species, such as sexual sterility and tolerance of high temperatures, that have been suggested as adaptations to riparian conditions. It appears to be widespread in Europe and has also been detected in Australia, New Zealand and the USA. It was shown to be weakly or moderately aggressive on inoculation to Alnus, Prunus and Salix. The extent of P. lacustris' activity as a saprotroph in plant debris in water and as an opportunistic pathogen in riparian habitats needs further investigation. Its pathogenic potential to cultivated fruit trees also deserves attention because P. lacustris has apparently been introduced into the nursery trade.